Disain kawasan binaan melalui riset (Kasus pemanfaatan potensi kawasan industri kerajinan tenun sebagai obyek wisata di Desa Poto, Moyohilir-Sumbawa Besar) - A. Tutut Subadyo; Junianto Junianto (University of Merdeka Malang, 2003)
Poto Village is a village that produces Ikat and Songket fabrics, which are typical fabrics of the Sumbawa region. During the royal era, Poto Village became a supplier of woven cloth to the Sumbawa Kingdom, for its nobility. Until now, the role as a supplier is still running, but for the general public. This weaving tradition is also supported by the culture of the local community that still survives. These cultural traditions are in the form of local folk arts, such as the Ponan Party (People's Party welcoming the rice planting season), Karapan Sapi, Horse Racing with jockeys aged 5-13 years. The setting of these activities has become a strong tourist attraction for the Sumbawa Besar area. Many of them are foreign tourists, not only wanting to see the results of woven fabrics but also seeing the manufacturing process and the traditional life of the local community. Through historical studies and architectural, environmental, and socio-cultural potentials of the community, the planning and design of Poto Village as a Tourism Village was carried out. From the analysis of the data obtained, a model of architectural and planology planning was made for the ikat industrial area in Poto Village. Based on the results, spatial settings are needed to be able to support the realization of Poto Village into a Craft Tourism Village.